(3eVGejf GdCee GdeJMOI hbjegG aj efGgL GdJQHjI GdhWfjI hGdJfTFI GdeOfjI hcJHgGs - (3ecj, eMeO cGXe s; (3NhQj, JjQjR JfhQj s; (3fYeI Gddg, gjcd s ((3HjQhJs (3GdeQcR GdJQHhj ddHMhK hGdEfeGAs, 2004)
(3JfGhd gPG GdJbQjQ efGgL GdJQHjI GdhWfjI hGdJfTFI GdeOfjI hcJHgG aj cd Ua haj cd eQMdI JYdjejI, aQUO GdeVGejf GdeYQajI hGdbjejI hJhRYgG aj cJH GdJQHjI GdhWfjI hGdJfTFI GdeOfjI, GdOQhS, OaGJQ GdJWHjbGJ hGdJeGQjf, hOdjd GdeYdejf, hfXe gPg GdeYWjGJ aj LOGhd EMUGFjI hHjGfjI, eY TQM JaGUjd TQYI Mbhb GdEfSGf hGdfUhU GdOhdjI GdNGUI HgG(B. (3EYJeO aj EYOGO gPG GdJbQjQ Ydi GdefgL GdJMdjdj, aHYO GdJejjR Hjf eVGejf GdCee GdeJMOI hHjf bjegG, Je JMOjO eUGOQ GdOQGSI GdOhdjI hGddHfGfjI, GdbGfhfjI hGdJfXjejI GdJQHhjI, hJMOjO GdcJH hHjGf YOOgG hGdehGUaGJ GdNGUI hGdeejRI dcd efgG heYQaI eOi JMbjb hXjaJgG GdJQHhjI(B. (3HYOgG Je JhRjY fJGFL GdOQGSI GdJMdjdjI Ydi Mbhd eJdGMbI heJcGedI aj LOhd hGMO, hJMOjO YfGhjf gPg GdMbhd, heGgjI cd Mbd heVGejfg Ef cGfJ eYQajI Ce bjejI(B. (3HjfJ GdfJGFL Cf ehGO EYdGf Mbhb GdEfSGf gj GdCcKQ eKhdG aj cJH GdJQHjI GdhWfjI aj GdJYdje GdCSGSj ef cJH GdJYdje GdKGfhj, hCf fUhU GdCee GdeJMOI GdJj Je GdQLhY EdjgG dG JbJUQ Ydi ejKGb GdCee GdeJMOI hTQYI Mbhb GdEfSGf, Hd Ef JfhY GdKbGaI aj dHfGf hZfGgG hGgJeGegG HGdbVGjG GdeUjQjI ddTYhH LYdgG JQLY Edi GdfUhU GdOhdjI GdeJYdbI HGdWad hHGdeQCI hGdbVGA Ydi GdLhY hGdJejjR GdYfUQj hESgGe hSGFd GdEYdGe aj OYe GdSdGe heTGQcI GdLeGgjQ GdTYHjI aj GdMjGI GdKbGajI hMbhb GdeYhbjf(B. (3hXgQ aj GdfJGFL bjGe fXGe JQHhj LOjO aj dHfGf YqHQ Yfg GdGgJeGe HGdCee GdeJMOI OGNd GdcJH, GdJj cqhfJ GdeUOQ GdChSY hGdCcKQ Zfi ddJQHjI GdhWfjI hGdJfTFI GdeOfjI aj dHfGf(B. (3HGdEVGaI Edi EecGfjI GdGSJYGfI dGMbG ef fJGFL gPG GdJbQjQ hHGdLOGhd GdedMbI Hg YfO EYGOI GdfXQ aj efGgL GdJYdje(B.s
(3GdfhY (B: (3JbQjQs
Keywords: Civic Education Curricula; Education Civique Curriculum; ONU; UN; (3GdGee GdeJMOIs; (3JYdje GdJQHjI GdhWfjI hGdJfTFI GdeOfjI GdefGgLs